Icariin inhibits the expression of IL-1β, IL-6 and TNF-α induced by OGD/R through the IRE1/XBP1s pathway in microglia - Zhen-Tao Mo; Jie Zheng; Yu-ling Liao (Taylor & Francis Group, 2021)
Context Icariin (ICA), a flavonol glycoside extracted from Epimedium brevicornum Maxim (Berberidaceae), has been proven to inhibit inflammatory response in ischaemic rats in our laboratory's previous work. However, its underlying mechanism is still unclear. Objective This study investigates the effects of ICA on endoplasmic reticulum (ER) stress mediated inflammation induced by cerebral ischaemia-reperfusion (I/R) injury in vitro. Materials and methods The primary cultured microglia were treated with oxygen-glucose deprivation (OGD) for 2 h followed by a 24 h reoxygenation. ICA (0.37, 0.74 and 1.48 μmol/L) administration was performed 1 h prior OGD and acting through 2 h OGD. The control group was cultured in normal conditions. At 24 h after reoxygenation, the expression of IRE1α, XBP1u, XBP1s, NLRP3 and caspase-1 was detected by western blotting (WB) and quantitative real-time (qRT) PCR; the expression of p-IRE1α was examined by WB; the expression of IL-1β, IL-6 and TNF-α was measured by WB and enzyme-linked immunosorbent assay (ELISA). Results ICA (0.37, 0.74 and 1.48 μmol/L) reduced the ratio of p-IRE1α/IRE1α, the mRNA level of IRE1α, the expression of XBP1u, XBP1s, NLRP3, caspase-1 at both the mRNA and protein level expression of IL-1β, IL-6 and TNF-α in OGD/R injured microglia. Overexpression of IRE1 significantly reversed the effects of ICA. Discussion and conclusions These results suggested that ICA might decrease the expression of IL-1β, IL-6 and TNF-α by inhibiting IRE1/XBP1s pathway. The anti-inflammatory effect of ICA may provide a potential therapeutic strategy for the treatment of brain injury after stroke.